ANALYSIS OF SKILLS OF POSYANDU COACHES IN PUSKESMAS AIR BELITI, MUSI RAWAS DISTRICT - Hari Agus Pranata; Akhmad Dwi Priyatno; Lilis Suryani; Helen Evelina; Syarifah Nadya Assegaf (LPPM STIKES Al-Ma'arif Baturaja, 2025)
In the era of Life Cycle Primary Care Confirmation, cadres are required to have Posyandu cadre skills. Posyandu cadre skills are very important to improve the quality of services in all life cycles ranging from infants and toddlers, pregnant women, adolescents, productive age and the elderly. Posyandu cadres in the Air Beliti Health Center area have never attended Posyandu cadre skills training. The research method uses a cross sectional design, the population is all posyandu cadres in 2025 using total sampling of 124 respondents. the test used is chi square test and logistic regression and multiple linear regression. The results obtained pvalue variable age 0.534 OR = 0.787, variable education 0.386 OR = 0.642, variable length of work 0.260 OR = 0.582, knowledge 0.000 OR = 31.182, cadre motivation 0.000 OR = 9.701. In conclusion, there is a significant relationship between the variables of knowledge and motivation of cadres, while the variables of age, education and length of service were not found to have a significant relationship with the skills of posyandu cadres. It is recommended that regular and continuous training be organized that focuses on the 25 basic skills of cadres, with a hands-on approach and evaluation of learning outcomes